FINE NEEDLE ASPIRATION CYTOLOGY OF THYROID NODULE: DIAGNOSTIC ACCURACY AND PITFALLS - Mahar, Saeed A.; Husain, Akhtar; Islam, Najmul (Journal of Ayub Medical College Abbottabad, 2006)
Objective : To evaluate the utility of FNAC in patients with Thyroid Nodule. Methods : Records of all patients treated surgically for thyroid nodule(s) at Aga Khan University Hospital from January 2000 to December 2004 were reviewed. The patients who had pre operative FNAC as first line of the evaluation and the final post operative histopathology report available were included in the study. Results: 125 patients (90 female 35 male) had thyroid surgery. The cytological diagnosis was made according to following categories: Benign, Follicular lesion, Malignant and Inadequate sampling. Among 63 Benign cases, 57 were benign and 6 turned out to be malignant. Among 44 cases from Follicular group, 31 were benign and 13 were malignant. Out of 15 patients from Malignant group, 14 were malignant and 1 was benign. Among three patients from the Inadequate sampling group, 2 turned out to be benign and one was malignant. The overall results showed a sensitivity of 98%, specificity of 70%, and positive predictive value of 91%, negative predictive value of 93% and diagnostic accuracy of 91%. Conclusion: We conclude that FNAC is an invaluable and minimally invasive procedure for pre operative assessment of patients with a thyroid nodule in our setting as well. FNAC has high sensitivity in picking up malignancy in thyroid and also has high diagnostic accuracy in the evaluation of thyroid nodules. Keywords : Thyroid - FNAC - Histopathology